2013
DOI: 10.15376/biores.8.3.4072-4087
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fermentation Conditions for Laccase Production by Recombinant Pichia pastoris GS115-LCCA Using Response Surface Methodology and Its Application to Dye Decolorization

Abstract: In this work, recombinant Pichia pastoris GS115-lccA was cultured and expressed with the highest laccase activity of 2357 U/L with ABTS (2, 2'-nazinobis-(3-ethylbenzthiazoline-6-sulphonate)) as reacting substrate. To achieve the higher laccase activity, multiple key factors were screened (using a Plackett-Burman design of experiments methodology) related to the fermentation conditions for producing GS115-lccA. Subsequently, a Box-Behnken response surface methodology was employed for further optimization. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
2
5
2
Order By: Relevance
“…With the addition of ammonium sulfate, zinc chloride, potassium chloride, and Tween surfactant, the lowest levels of laccase activity were obtained (94,111,47, and 23 U⋅L −1 , respectively; data not shown). In this sense, in agreement with our results, Bao et al (2013) reported zinc, potassium, and ammonium (tested on purified enzyme) as inhibitors of recombinant laccase, and Li et al (2013) found that ammonium and zinc had no significant effect on recombinant laccase activity. However, the effects of different compounds on laccase activity were not always the same; Bao et al (2013) also reported iron as an inhibitor and Tween as an inducer of recombinant laccase, Tülek et al (2020) said that high concentrations of iron significantly inhibited laccase activity, while zinc and magnesium caused an increase in laccase activity, and Li et al (2013) stated that a recombinant enzyme was completely inactivated with iron, as opposed to our We elucidated that the differences in laccase activity obtained with each compound could be due to the difference in chemical structures, which affects the folding of laccase and significantly increase or decrease the activity.…”
Section: Effect Of Compounds On Laccase Activitysupporting
confidence: 90%
“…With the addition of ammonium sulfate, zinc chloride, potassium chloride, and Tween surfactant, the lowest levels of laccase activity were obtained (94,111,47, and 23 U⋅L −1 , respectively; data not shown). In this sense, in agreement with our results, Bao et al (2013) reported zinc, potassium, and ammonium (tested on purified enzyme) as inhibitors of recombinant laccase, and Li et al (2013) found that ammonium and zinc had no significant effect on recombinant laccase activity. However, the effects of different compounds on laccase activity were not always the same; Bao et al (2013) also reported iron as an inhibitor and Tween as an inducer of recombinant laccase, Tülek et al (2020) said that high concentrations of iron significantly inhibited laccase activity, while zinc and magnesium caused an increase in laccase activity, and Li et al (2013) stated that a recombinant enzyme was completely inactivated with iron, as opposed to our We elucidated that the differences in laccase activity obtained with each compound could be due to the difference in chemical structures, which affects the folding of laccase and significantly increase or decrease the activity.…”
Section: Effect Of Compounds On Laccase Activitysupporting
confidence: 90%
“…Furthermore it has also been reported that H.Insulare HD is able to grow and decolorize diluted pesticide wastewater only in the presence of a complex medium containing nutrients, and vertebral alcohol as inducer of ligninolytic enzymes [10]. On the other hand, our results prove that the absence of added nutrients does not significantly reduce the ability of H.Insulare to decolorize pesticide wastewater.…”
Section: Discussionsupporting
confidence: 74%
“…They achieved a laccase yield of 55.4 U/g using an RSM approach. In our study, the maximum laccase yield of 607.2 U/mL was much higher than that obtained in other recent studies (Niladevi et al, 2009;Li et al, 2013). The rate of wheat straw degradation obtained in this study was also higher than that reported elsewhere.…”
Section: Optimization Of Fermentation Conditions (Rsm Ii)contrasting
confidence: 73%